2022
DOI: 10.3390/app12094367
|View full text |Cite
|
Sign up to set email alerts
|

Deposition and Mobilization of Microplastics in a Low-Energy Fluvial Environment from a Geomorphological Perspective

Abstract: Though microplastic (MP/MiP) pollution of the environment is a popular research topic, a relatively limited number of studies are investigating its geomorphological context. However, site-specific hydrological and morphological parameters fundamentally affect the MP transport, deposition and mobilization. Therefore, we aimed to evaluate the geomorphological influencing factors on MP deposition in the fluvial sediments of the Tisza River (Central Europe). Between the two surveys (in 2019 and 2020), small flood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(37 citation statements)
references
References 53 publications
4
33
0
Order By: Relevance
“…One of the first complex measurements was carried out by Hurley et al [13], who found that floods effectively redistribute MP pollution within a river system, though this is not spatially uniform. A similar redistribution was observed by Rodrigues et al [20] and Kiss et al [14,21]. Thus, spatially and temporally repeated measurements could be used to identify MP sources and the origin of the pollution, transport and mixing of MPs, their accumulation, hotspot deployment and the main driving factors of these processes.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…One of the first complex measurements was carried out by Hurley et al [13], who found that floods effectively redistribute MP pollution within a river system, though this is not spatially uniform. A similar redistribution was observed by Rodrigues et al [20] and Kiss et al [14,21]. Thus, spatially and temporally repeated measurements could be used to identify MP sources and the origin of the pollution, transport and mixing of MPs, their accumulation, hotspot deployment and the main driving factors of these processes.…”
Section: Introductionsupporting
confidence: 72%
“…The concentration of MP particles transported in rivers is neither spatially nor temporally constant [13,14], as the points could act as sinks or sources [6]. Spatial monitoring, e.g., sampling multiple sites within a water system at a given time, is common [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The microplastic content of sediments of the Tisza and its tributaries has been studied systematically since 2019 [30][31][32][33][34][35]. Each summer, a sampling campaign was performed from the source of the Tisza in Ukraine to its confluence in Serbia and in the near-confluence sections of the main tributaries.…”
Section: Former Data On Riverine Litter and Microplastic Fragments In...mentioning
confidence: 99%
“…The MaP pollution of the Tisza and the mountainous areas of the catchment were documented by Liro et al [16], Mohsen et al [22] and Magyar et al [27]. Besides, one of the longest and most detailed microplastic surveys of the world was performed in the river system of the Tisza, revealing the MiP transport in the river and its accumulation in the sediments [30][31][32][33][34][35].…”
mentioning
confidence: 96%
See 1 more Smart Citation